Exploring the Role of Techno-stress in Job Performance of Academic Librarians of Lahore Pakistan - Sabzwari, Muhammad; Suqlain, Shazia; Khan, Fauzdar (Pakistan Journal of Humanities and Social Sciences, 2023)
Rapid changes in technology have affected all walks of life. Role of Techno-stress in job performance of academic librarians is the facts and impact on employees with higher stress levels. This paper studies four dimensions of techno-stress among academic librarians of Public and Private Colleges of Lahore in Punjab Province. Quantitative approach for this study was used with survey method and non-probability sampling technique was employed on population. Those 50 public and private colleges in Lahore were chosen, from which 180 academic librarians were the part of study. Online survey questionnaire was conducted. Frequencies, percentage, mean, standard deviation, correlation, t-test and regression was used for data analysis through SPSS. Results of this research carried out to study techno-stress, it described college librarians experienced moderate level of techno-stress in their job performance. There was particular difference found between male and female college librarians in terms of techno stress. The findings, however, show that techno-overload and techno uncertainty has negative effect on job-performance of female librarians.